Energetic analysis of the molecular packing of 5, 5′‐dibromo‐2, 2′‐bis[4‐(methylsulfanyl)phenyl]‐4, 4′‐bipyridine: the role of π–π and halogen interactions. (4th January 2013) - Abboud, Mohamed; Mamane, Victor; Aubert, Emmanuel
Abstract : The crystal packing of the title compound, C24 H18 Br2 N2 S2, is rationalized using the PIXEL method, which allows a separation of the intermolecular interaction energy into Coulombic, polarization, dispersion and repulsion contributions. Infinite ( 01) molecular planes are formed through π–π stacking and other minor interactions, including a Br...S contact, with the σ hole of the Br atom pointing towards the S‐atom lone pair. The title compound has crystallographically imposed twofold symmetry, with the twofold axis at the mid‐point of the central C—C bond.